Tele‐Derm National: A decade of teledermatology in rural and remote Australia. (18th December 2015) - Byrom, Lisa; Lucas, Lex; Sheedy, Vicki; Madison, Kim; McIver, Lachlan; Castrisos, George; Alfonzo, Christina; Chiu, Frank; Muir, Jim
Abstract: Objective: To identify the current scope of Tele‐Derm, the types of dermatological complaints experienced in the rural primary care setting, and to assess the quality of patient clinical information provided to the consultant dermatologist. Design: Retrospective case analysis. Setting: Tele‐Derm National is an initiative of the Australian College of Rural and Remote Medicine and has been providing online educational and consultational services in dermatology to doctors Australia‐wide for over a decade. Participants: Patient cases that were submitted to Tele‐Derm for specialist dermatologist advice. Interventions: Audit of submitted cases. Main outcome measures: The types of patient presentations and reason for submission for specialist opinion were analysed. The quality of clinical information provided was also evaluated. Results: A total of 406 cases submitted over 2012–2013 were analysed. Most patients were from the outpatient setting with 'rash' or dermatitis (66%). Almost one‐third of patients were paediatric cases. The average time from submission to dermatologist reply was 5.5 hours. Clinical photos were provided in 83% of cases and 73% of these were assessed as being of good quality. Management advice was provided in 77% of cases, of which reference to the case‐based learning modules on Tele‐Derm was made in 21% of cases. Patient outcome was largely unknown (83%). Conclusion: This study identified some of the common dermatological complaints presenting to rural and remote primary care doctors in Australia. The unique addition of professional development in Tele‐Derm can be used as an adjunct to advice provided to the rural doctors seeking advice for patient management.